The Improving of Intelligence Verbal-Linguistic Ability on Singing Method at the Group B of Pantai Indah Kindergarten, North Buton RegencyÃ¢â‚¬Â - Salwiah, Salwiah; Asmuddin, Asmuddin (Indonesian Journal of Early Childhood Education Studies, 2021)
The formulation of the problem is whether the intelligence of verbal-linguistic ability can be improved on singing method at the group B pantai indah kindergarten north regency, southeast sulawesi? The purpose of this study was to improve verbal of linguistic ability on singing method in B group pantai indah kindergarten north buton regency, southeast sulawesi. This type of the research is Classroom Action Research. This research was conducted in two cycles. The stages in this study follow the classroom action research procedures, namely: (1) planning, (2) implementation, (3) observation, (4) reflection. The subjects in this study were teachers and students in group B pantai indah kindergarten, amounting to 22 children consist of 7 girls and 15 boys. Based on the results of data analysis of teachers teaching activities in the first cycle as many as 15 aspects obtained a percentage of 86.7% or 13 aspects achieved, the students learning activities in the first cycle as many as 15 aspects obtained a percentage of 80% or 12 aspects achieved and from the results of children’s learning obtained a percentage of 63.6%. The results of the analysis of data teacher teaching activity in the second cycle have increased with the percentage obtained 93.3% in the learning activities of students in the second cycle obtained a percentage of 93.3% and children learning outcomens in improving verbal abilities on singing method in the second cycle was achieved with a percentage amounted to 86.4%. Thus it can be concluded that intelligence of verbal-linguistic ability can be improved on singing methods at the group B pantai indah kindergarten north regency southeast sulawesi.